Species delimitation of the white‐tailed rubythroat Calliope pectoralis complex (Aves, Muscicapidae) using an integrative taxonomic approach - Yang Liu; Guoling Chen; Qin Huang; Chenxi Jia; Geoff Carey; Paul Leader; Yun Li; Fasheng Zou; Xiaojun Yang; Urban Olsson; Per Alström (Journal of Avian Biology, 2016)
Our knowledge of the systematics and taxonomy of Asian birds has improved much in the last two decades, and the number of recognised species has increased significantly as a result of in‐depth studies using an integrative taxonomic approach. The Sino‐Himalayan mountains harbor a high level of passerine diversity. Several allopatric or parapatric taxa that are currently treated as subspecies of polytypic species within that region are likely to deserve full species status, and thus their taxonomic status needs to be revisited. Based on analyses of multilocus data, vocalizations and morphology, we propose that the white‐tailed rubythroat Calliope pectoralis should be treated as two species, the Himalayan rubythroat C. pectoralis sensu stricto in the Tian Shan and Himalayan mountains, and the Chinese rubythroat C. tschebaiewi in the mountains of southwestern and north‐central China. According to our dating analyses based on mitochondrial loci, these two species diverged approximately 2.2 million yr ago. We further found that C. tschebaiewi was paraphyletic to C. pectoralis sensu stricto in nuclear data, which demonstrates a state of mitonuclear discordance that warrants further work. Our results suggest that geographic changes and glacial cycles in the Pleistocene may have caused allopatric divergence in the C. pectoralis complex. Our study stresses the importance of applying an integrative taxonomy approach to fully unravel the true avian diversity in the Sino‐Himalayan Mountains.